Type 2 diabetes and glucose intolerance in a population with intellectual disabilities: the STOP diabetes cross‐sectional screening study. Issue 7 (21st May 2017) - Dunkley, A. J.; Tyrer, F.; Gray, L. J.; Bhaumik, S.; Spong, R.; Chudasama, Y.; Cooper, S.‐A.; Ganghadaran, S.; Davies, M.; Khunti, K.
Abstract: Background: Adults with intellectual disabilities (ID) may be at increased risk of developing type 2 diabetes and cardiovascular disease, due to lifestyle factors, medications and other diagnosed conditions. Currently, there is lack of evidence on prevalence and prevention in this population. The aim of this study was to conduct a diabetes screening programme to determine prevalence of previously undiagnosed type 2 diabetes and impaired glucose regulation in people with ID. Methods: Screening was conducted in a variety of community settings in Leicestershire, UK. Adults with ID were invited via: general practices; the Leicestershire Learning Disability Register; ID psychiatric services; and some people directly contacted the research team due to publicity about the study. Screening involved collection of anthropometric, biomedical and questionnaire data. Type 2 diabetes and impaired glucose regulation were defined according to (venous) fasting plasma glucose or HbA1c, following current World Health Organisation criteria. Results: Nine hundred thirty adults (29% of those approached) participated. Mean age was 43 years, 58% were male and 16% of South Asian ethnicity. Most participants were either overweight or obese (68%). Diabetes status was successfully assessed for 675 (73%) participants: Nine (1.3%, 95% confidence interval 0.6 to 2.5) were found to have undiagnosed type 2 diabetes, and 35 (5.2%, 95% confidence interval 3.6 to 7.1) had impaired glucose regulation. Key factors associated with abnormal glucose regulation included the following: non‐white ethnicity and a first degree family history of diabetes. Conclusions: Results from this large multi‐ethnic cohort suggest a low prevalence of screen‐detected (previously undiagnosed) type 2 diabetes and impaired glucose regulation in adults with ID. However, the high levels of overweight and obesity we found emphasise the need for targeted lifestyle prevention strategies, which are specifically tailored for the needs of people with ID.